L’eau, tout simplement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
L’Eau: Gérer localement Par D B Brooks, CRDI, 2002. 80 pages. ISBN 0889369976 CAD 15 • 9, 95 CRDI BP 8500, Ottawa, Ontario, Canada K1G 3H9 E-mail : pubs@idrc.ca Texte disponible gratuitement : www.idrc.ca/eau